Distinct patterns of microsatellite instability are seen in tumours of the urinary tract. - Catto, J; Azzouzi, A; Amira, N; Rehman, I; Feeley, K; Cross, S; Fromont, G; Sibony, M; Hamdy, F; Cussenot, O; Meuth, M (2003)
To date, two forms of microsatellite instability (MSI) have been described in human cancer. MSI typical of hereditary nonpolyposis colon cancer (HNPCC), is due to deficient DNA mismatch repair (MMR) and is defined with mono- and dinucleotide repeat microsatellites. A second variety of instability is best seen at selective tetranucleotide repeats (EMAST; elevated microsatellite alterations at select tetranucleotides). While MSI occurs infrequently in bladder cancers, EMAST is common. Sporadic tumours with the largest proportion showing MSI are those found most frequently in HNPCC kindreds. While bladder cancer is not frequently seen in HNPCC, upper urinary tract tumours (UTTs) are. Having previously found a low frequency of MSI in bladder cancer, we sought to determine the relative levels of MSI and EMAST in transitional cell carcinoma (TCC) of the upper and lower urinary tracts. Microsatellite analysis was performed at 10 mono- and dinucleotide and eight tetranucleotide loci, in 89 bladder and 71 UTT TCC. Contrasting patterns of instability were seen in urinary tumours. In bladder cancer, MSI was rare and EMAST was common. The presence of EMAST was not related to tumour grade, stage, subsequent outcome or immunohistochemical expression of the MMR proteins. In UTT, while MSI occurred frequently, EMAST was seen less frequently than in bladder cancer. When TCC of the upper and lower urinary tracts are compared, MSI-H is more frequent in UTT and EMAST more frequent in bladder cancer. Our findings show that, as for colorectal cancer, the pattern of MSI varies with location in the urinary tract. In addition, we have confirmed that MSI and EMAST are discrete forms of MSI, and that the presence of EMAST does not affect tumour phenotype.